The Existence of Multiple Periodic Solutions of Nonautonomous Delay Differential Equations - Huafeng Xiao; Bo Zheng (Journal of Applied Mathematics)
We study the multiplicity of periodic solutions of nonautonomous delay differential equations which are asymptotically linear both at zero and at infinity. By making use of a theorem of Benci, some sufficient conditions are obtained to guarantee the existence of multiple periodic solutions.